Implementation of some remedial actions to improve the performance and level of transit service for public transport bus routes in Baghdad city - Abbas, Imad Ismael; Diwood, Noor Mukdam; Naser, Ali Fadhil (Penerbit Universiti Kebangsaan Malaysia, 2022)
The objective of this study was to improve level of transit service of public transport bus routes in Baghdad city through the implementation of some remedial actions. Eight public transport bus routes were selected to evaluate and improve the Level of Transit Service (LOTS). These routes represent Al-Tahrir bus network (A) which was located in the center of Baghdad city (capital of Iraq). The suggested remedial actions include reduction of legal bus stops delay (B), the elimination of illegal bus stops delay (b), the elimination of signalized intersections delay (I), and the reduction of traffic congestion delay (C). These suggested remedial actions are leaded to improve the values of total delay, bus travel time, service frequency (headway), adjusted running speed, and capacity. The values of level of transit service for these transit performance measures were improved. The overall routes level of transit service were improved for bus routes No. (72, 36, 13, 114, 11, 30, 37, and 9) from LOTS (D, E, E, E, E, D, E, and E) to LOTS (C, D, C, D, D, C, D, and D) respectively. The overall network LOTS was improved from LOTS (E) to LOTS (D), indicating that the application of the suggested remedial actions was effective and suitable to improve the performance and Level of Transit Service for public transport bus routes in Baghdad city. Therefore, this study recommended to use the remedial actions which proposed by authors to improve level of transit service for others bus networks.